2011
DOI: 10.1097/mph.0b013e3182025507
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypoglycemic Seizures in a Child Receiving 6-Mercaptopurine

Abstract: A 4-year-old boy with acute lymphoblastic leukemia who was receiving 6-mercaptopurine during the maintenance chemotherapy experienced prolonged generalized tonic nocturnal seizures because of severe hypoglycemia after his evening dose by a 12-hour period of fasting. Investigations ruled out all causes of these seizures other than the 6-mercaptopurine-induced severe hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Symptomatic hypoglycemia due to 6-MP is one of its rare side effects, and only a few cases have been reported. El-Bitar et al [6] reported prolonged generalized tonic nocturnal seizures and severe hypoglycemia in a 4-year-old boy who was diagnosed with ALL and received 6-MP as maintenance therapy. The symptoms occurred after taking the evening dose of 6-MP after a 12-hour period of fasting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptomatic hypoglycemia due to 6-MP is one of its rare side effects, and only a few cases have been reported. El-Bitar et al [6] reported prolonged generalized tonic nocturnal seizures and severe hypoglycemia in a 4-year-old boy who was diagnosed with ALL and received 6-MP as maintenance therapy. The symptoms occurred after taking the evening dose of 6-MP after a 12-hour period of fasting.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the literature, this condition was treated with a similar approach, and hypoglycemia was found to be improved [3,5,11]. For children aged under 6 years in particular, it is recommended to wake up and drink milk or juice after 8 to 9 hours of sleep [6,8]. If hypoglycemic symptoms are very severe, the dose of 6-MP may be reduced for a short period of time [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that 6-MP, when used to treat leukemia in children, has resulted in unexplained symptomatic hypoglycemia (7,12,44). In this study, we found that 6-MP was able to augment glucose transport and GLUT4 translocation in basal muscle cells even in the absence of insulin.…”
Section: Discussionmentioning
confidence: 89%
“…Thus far, these methods have only been reported in patients experiencing hypoglycemia. Two cases demonstrated complete reversal of symptoms with changes in timing of 6-MP administration plus a carbohydrate-enriched diet, whereas these methods failed to resolve hypoglycemic episodes in two other reports (25)(26)(27)(28). A fifth case required 6-MP dose reduction in addition to morning administration to achieve the desired response (29).…”
Section: Clinical Use Of Allopurinol To Mitigate 6-mp Toxicity Duringmentioning
confidence: 96%